Actin-binding protein regulation by microRNAs as a novel microbial strategy to modulate phagocytosis by host cells: the case of N-Wasp and miR-142-3p - Bettencourt, Paulo; Marion, Sabrina; Pires, David; Santos, Leonor; Lastrucci, Claire; Carmo, Nuno; Blake, Jonathon; Benes, Vladimir; Griffiths, Gareth; Neyrolles, Olivier; Lugo-Villarino, Geanncarlo; Anes, Elsa (Frontiers in Cellular and Infection Microbiology, 2013)
Mycobacterium tuberculosis (Mtb) is a successful intracellular pathogen that thrives in macrophages (Mφs). There is a need to better understand how Mtb hijacks cellular processes like phagolysosome biogenesis, a classical pathogenesis determinant. A central feature to this microbial strategy is the manipulation of actin in Mφs. Here, we examine the role of microRNAs (miRNAs) as a potential mechanism in the regulation of actin-mediated events leading to phagocytosis in the context of mycobacteria infection. Given that non-virulent Mycobacterium smegmatis also controls actin filamentation to prolong its instracellular survival inside host cells, our approach was to perform a global transcriptomic approach to assess the modulation of miRNAs upon M. smegmatis infection of the murine Mφ cell line, J774A.1. This approach yielded miR-142-3p as a top candidate to be involved in the regulation of actin dynamics required in phagocytosis. We unequivocally demonstrate miR-142-3p targets N-Wasp, an actin-binding protein required during microbial challenge. A gain-of-function approach for miR-142-3p revealed a down-regulation of N-Wasp expression accompanied by a decrease of mycobacteria intake, while a loss-of-function approach yielded the reciprocal increase of the phagocytosis process. Equally important, we show Mtb induces the early expression of miR-142-3p and down-regulates N-Wasp protein levels in both the murine J774A.1 cell line and primary human Mφs. As proof of principle, the partial siRNA-mediated knock down of N-Wasp resulted in a decrease of Mtb intake by human Mφs, reflected in lower levels of colony-forming units counts over time. We therefore propose the modulation of miRNAs as a novel strategy in mycobacterial infection to control factors involved in actin filamentation and other early events of phagolysosome biogenesis, such as the case presented here for miR-142-3p influencing N-Wasp activity during the phagocytosis process.